Dynamic Analysis of Monetary and Fiscal Policy Mix on Inflation and Unemployment in Indonesia - WAHYU INDAH SARI; Sirojuzilam Hasyim; M. Syafii (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2025)
This study aims to analyze the dynamic interactions between monetary and fiscal policies and their effects on inflation and unemployment in Indonesia. The study employs a Vector Autoregression (VAR) approach using annual data from 2000 to 2024. The variables include the policy interest rate (BI Rate), inflation, unemployment, GDP growth, government expenditure, exchange rate, and tax revenue. The unit root tests indicate that the variables exhibit a combination of I(0) and I(1) integration orders, while the Johansen cointegration test confirms the existence of a long-run equilibrium relationship among the variables. The optimal lag length is determined to be two, and the stability test confirms that the VAR model is stable. The Granger causality test reveals that the BI Rate significantly Granger-causes inflation and unemployment, whereas reverse causality is not supported. In addition, inflation is found to Granger-cause unemployment, and fiscal as well as external variables—government expenditure, tax revenue, and exchange rate—significantly affect inflation. The Impulse Response Function (IRF) results show that a positive shock to the policy interest rate gradually reduces inflation but leads to a short-run increase in unemployment. Furthermore, the Forecast Error Variance Decomposition (FEVD) indicates that inflation variability is largely driven by monetary policy shocks, while unemployment and economic growth fluctuations are mainly explained by fiscal policy and internal economic dynamics. These findings highlight the importance of strong coordination between monetary and fiscal policies to maintain macroeconomic stability in Indonesia.